ELECTRONIC LIBRARY SYSTEMS AND MEDIA-REVOLUTION - Pavel Yu. Kallinikov (Высшее образование в России)
The article focuses on the issues of development of Electronic Library Systems in conditions of changing the content circulation and content management. The growth of social metabolism activated by the development of the Global network causes the changes in the authorship relations so long as publication ceases to be a privileged occupation and becomes accessible, free and effective for everybody. So the designers of Electronic Library Systems in order toretain the users should provide them with the better search and selection technologies,semantic content analysis.